Adaptive Cueing Treatment of Neglect in Stroke Patients Leads to Improvements in Activities of Daily Living: A Randomized Controlled, Crossover Trial. (November 2018) - Turgut, Nergiz; Möller, Lisa; Dengler, Kerstin; Steinberg, Katrin; Sprenger, Andreas; Eling, Paul; Kastrup, Andreas; Hildebrandt, Helmut
Background . Visuospatial neglect is a disabling syndrome with serious consequences for activities in daily life. This study investigated the effect of adaptive cueing during a reading task as a possible treatment for neglect by including (1) a task relevant for the patient's daily life, (2) a fading out procedure to stimulate independent orientation to the left by self-cueing, and (3) a clear definition of neglect severity for the adaptive treatment protocol. Methods . A randomized controlled crossover design was used, including 26 patients from an early rehabilitation unit with left-sided visuospatial neglect after stroke or hemorrhage. They were examined twice at baseline (T1, T2), after 15 daily sessions in 1 condition (T3), and again after 15 daily sessions in the other condition (T4). The intervention condition included a daily reading task combined with endogenous and exogenous cues provided by a therapist, which were continuously reduced after a patient had reached a defined level of performance. The control condition consisted of a neuropsychological treatment of the same length, not targeting visuospatial attention. Results . Significant improvements were shown after intervention on scores for reading (word and text reading), daily life activities (Catherine Bergego Scale), Line Bisection, and the Clock Drawing Task. Conclusion . This study shows that adaptive cueing in a reading task can improve neglect symptoms by using an intensive intervention lasting 3 weeks.